Irreversible Oxidation of the Active-site Cysteine of Peroxiredoxin to Cysteine Sulfonic Acid for Enhanced Molecular Chaperone Activity - Lim, Jung Chae (American Society for Biochemistry and Molecular Biology, 2008)
The thiol (–SH) of the active cysteine residue in peroxiredoxin (Prx) is known to be reversibly hyperoxidized to cysteine sulfinic acid (–SO(2)H), which can be reduced back to thiol by sulfiredoxin/sestrin. However, hyperoxidized Prx of an irreversible nature has not been reported yet. Using an antibody developed against the sulfonylated (–SO(3)H) yeast Prx (Tsa1p) active-site peptide (AFTFVCPTEI), we observed an increase in the immunoblot intensity in proportion to the H(2)O(2) concentrations administered to the yeast cells. We identified two species of hyperoxidized Tsa1p: one can be reduced back (reversible) with sulfiredoxin, and the other cannot (irreversible). Irreversibly hyperoxidized Tsa1p was identified as containing the active-site cysteine sulfonic acid (Tsa1p-SO(3)H) by mass spectrometry. Tsa1p-SO(3)H was not an autoxidation product of Tsa1p-SO(2)H and was maintained in yeast cells even after two doubling cycles. Tsa1p-SO(3)H self-assembled into a ring-shaped multimeric form was shown by electron microscopy. Although the Tsa1p-SO(3)H multimer lost its peroxidase activity, it gained ∼4-fold higher chaperone activity compared with Tsa1p-SH. In this study, we identify an irreversibly hyperoxidized Prx, Tsa1p-SO(3)H, with enhanced molecular chaperone activity and suggest that Tsa1p-SO(3)H is a marker of cumulative oxidative stress in cells.